Golden Hope Plantations Berhad: which project to invest? - Senik, Rosmila; Mat Daud, Zaidi; Mohamed, Zainal Abidin; Zubir, Mohamad Shahnaz (Universiti Putra Malaysia Press, 2011)
This is a case on capital budgeting project. Golden Hope Plantations Berhad (GHPB), was located at Menara PNB, Jalan Tun Razak, Kuala Lumpur, Malaysia and was listed on the first board of Bursa Saham Malaysia. GHPB was desirous to expand its operations using its available internal fund. The company had two available options for its business expansions; purchase of the last piece of freehold land in Shah Alam, Malaysia suitable for property development and the other was purchase of a refinery facility in the Netherlands. Both options presented different opportunities that brought favorable revenue to the company; however both options required substantial amount of internal cash for their acquisition. The Board of Director (BOD) needed to consider both options in order to choose the one that would bring the best return to the company and enhance the shareholder’s value. This case demonstrates how Strength, Weakness, Opportunity and Threat (SWOT) analysis and financial analysis can help management to select the best investment alternative.